2013
DOI: 10.3109/10408363.2013.805182
|View full text |Cite
|
Sign up to set email alerts
|

Pterostilbene: Biomedical applications

Abstract: Resveratrol and its naturally dimethylated analog, pterostilbene, show similar biological activities. However, the higher in vivo bioavailability of pterostilbene represents a fundamental advantage. The main focus of this review is on biomedical applications of pterostilbene. The metabolism and pharmacokinetics of this stilbene in inflammatory dermatoses and photoprotection, cancer prevention and therapy, insulin sensitivity, blood glycemia and lipid levels, cardiovascular diseases, aging, and memory and cogni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(130 citation statements)
references
References 154 publications
3
127
0
Order By: Relevance
“…In another study, resveratrol was demonstrated to enhance the apoptotic potential of perifosine and bortezomib in drug-refractory MM and T-cell leukemia cells by enhancing recruitment of Fas/CD95 death receptors in the extrinsic pathway of apoptosis (26). Compared with resveratrol, Pter has similar pharmacologic benefits but exhibits much greater bioavailability (95% vs. 20%) and much longer half-life (105 vs. 14 min), which makes it more potent for clinical use (10). Pter was found to inhibit growth of chemoresistant human bladder-cancer cells by inducing cell cycle arrest, autophagy and apoptosis (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another study, resveratrol was demonstrated to enhance the apoptotic potential of perifosine and bortezomib in drug-refractory MM and T-cell leukemia cells by enhancing recruitment of Fas/CD95 death receptors in the extrinsic pathway of apoptosis (26). Compared with resveratrol, Pter has similar pharmacologic benefits but exhibits much greater bioavailability (95% vs. 20%) and much longer half-life (105 vs. 14 min), which makes it more potent for clinical use (10). Pter was found to inhibit growth of chemoresistant human bladder-cancer cells by inducing cell cycle arrest, autophagy and apoptosis (12).…”
Section: Discussionmentioning
confidence: 99%
“…Various drug-resistant tumors, including lung carcinoma, pancreatic cancer, acute myeloid leukemia, promyelocytic leukemia, and MM, can be sensitized by resveratrol (6)(7)(8)(9). Pterostilbene (3,5-dimethoxy-40-hydroxystilbene; Pter) is found mainly in blueberries, grapes and tree wood (10). Pter is a natural dimethylated analog of resveratrol but is superior to the latter with regard to liposolubility and bioavailability, which potentially makes it a more potent anticarcinogenic compound than resveratrol (10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resveratrol and piceatannol derivatives were detected in herbaceous plants, shrubs, lians, and trees (Polygonaceae, Fabaceae, Ericaceae, Vitaceae, Pinaceae, Gnetaceae, and others). T-resveratrol, and to a lesser extent t-piceatannol and t-pterostilbene, are the most renowned stilbenes for their beneficial properties (Kalantari and Das 2010;Piotrowska et al 2012;Estrela et al 2013) and, therefore, attract special attention. Among the analyzed plant species, knotweed (roots) produces the highest amounts of t-resveratrol, while gnetum (roots), myrtle (sim fruit), and rhubarb (roots) produce the highest amounts of tpiceatannol (Table 1).…”
Section: Stilbene Distribution Contents and Localizationmentioning
confidence: 99%
“…Resveratrol and its derivatives ( Fig. 1), such as pterostilbene, oxyresveratrol, or viniferins, are the most famous stilbenes due to their diverse potent biological activities and medicinal properties and have been extensively studied (Kalantari and Das 2010;Pangeni et al 2014;Estrela et al 2013;Xu et al 2014;Wang and Yao 2015). Resveratrol has been shown to possess antioxidant, immunomodulatory, anti-inflammatory, and antiangiogenic effects and a wide range of health benefits, such as cancer chemoprevention or cardioprotection (Kalantari and Das 2010;Pangeni et al 2014;Weiskirchen and Weiskirchen 2016).…”
Section: Introductionmentioning
confidence: 99%